FACTORS INFLUENCING THE DEVELOPMENT OF INDUSTRIES IN THE INDUSTRIAL SECTOR OF THE ECONOMY (World Economics and Finance Bulletin, 2024)
The importance and role of the industrial sector in the development of the country's economy are highlighted. The issues of stable development of the industrial sector in the national economy of Uzbekistan, innovative activity of the industry, as well as management efficiency were touched upon. The analysis showed that as a result of the measures taken to reform the economy, a number of positive changes were achieved in the structural changes carried out in the industrial complex. The main factors of industrial development are identified
Keywords: Industry; Industryefficiency